Removal of Oxide Nanoparticles in a Model Wastewater Treatment Plant: Influence of Agglomeration and Surfactants on Clearing Efficiency - Limbach, Ludwig K; Bereiter, Robert; Müller, Elisabeth; Krebs, Rolf; Gälli, René; Stark, Wendelin J (Environmental science & technology, 2008)
The rapidly increasing production of engineered nanoparticles has created a demand for particle removal from industrial and communal wastewater streams. Efficient removal is particularly important in view of increasing long-term persistence and evidence for considerable ecotoxicity of specific nanoparticles. The present work investigates the use of a model wastewater treatment plant for removal of oxide nanoparticles. While a majority of the nanoparticles could be captured through adhesion to clearing sludge, a significant fraction of the engineered nanoparticles escaped the wastewater plant’s clearing system, and up to 6 wt % of the model compound cerium oxide was found in the exit stream of the model plant. Our study demonstrates a significant influence of surface charge and the addition of dispersion stabilizing surfactants as routinely used in the preparation of nanoparticle derived products. A detailed investigation on the agglomeration of oxide nanoparticles in wastewater streams revealed a high stabilization of the particles against clearance (adsorption on the bacteria from the sludge). This unexpected finding suggests a need to investigate nanoparticle clearance in more detail and demonstrates the complex interactions between dissolved species and the nanoparticles within the continuously changing environment of the clearing sludge.